Assessment of NASA's Mars Architecture 2007-2016 - National Research Council (The National Academies Press, 2006)
The United States and the former Soviet Union have sent spacecraft to mars as early as 1966, with Mars' exploration being priority for NASA spacecraft. Both sides, however, have failed as well as succeed. The inability to determine if life exists on Mars is considered one of NASA's failures and undercut political support for additional Mars missions in the U.S. until the launch of the Mars Observer in 1992. Thus, the exploration of life on Mars continues, but with a new approach.
Keywords: Space and Aeronautics

Opportunities to Address Clinical Research Workforce Diversity Needs for 2010 - Institute of Medicine; National Research Council (The National Academies Press, 2006)
Based on a 2003 workshop, this study describes current public and private programs and recommends ways to recruit and retain more women and underrepresented minorities into clinical research, especially physician-scientists and nurses. Federal sponsors should improve data collection, evaluate existing training programs, and increase the diversity of study section review panels. Public and private sponsors should create funding mechanisms with flexible career paths, and universities and professional societies should both play enhanced roles in fostering diversity. A significant push is needed to recruit minorities into nursing and provide more clinical research training for nurse-scientists, nursing students, and nursing faculty.
Keywords: Health and Medicine; Industry and Labor

The Richard and Hinda Rosenthal Lectures 2004: Perspectives on the Prevention of Childhood Obesity in Children and Youth - Institute of Medicine; Institute of Medicine (The National Academies Press, 2006)
In 1988, an exciting and important new program was launched at the Institute of Medicine (IOM). Through the generosity of the Richard and Hinda Rosenthal Foundation, a lecture series was established to bring to greater attention some of the critical health policy issues facing our nation today. Each year a subject of particular relevance is addressed through three lectures presented by experts in the field. The lectures are published at a later date for national dissemination.
Keywords: Health and Medicine; Computers and Information Technology

Space Studies Board Annual Report 2005 (The National Academies Press, 2006)

Report of the Treasurer to the Council for the Year Ended December 31, 2005 - National Academy of Sciences (The National Academies Press, 2006)

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2005 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2006)
This volume includes 16 papers from the National Academy of Engineering's 2005 U.S. Frontiers of Engineering (USFOE) Symposium held in September 2005. USFOE meetings bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2005 symposium covered four topic areas: ID and verification technologies, engineering for developing communities, engineering complex systems, and energy resources for the future. A paper by dinner speaker Dr. Shirley Ann Jackson, president of Rensselaer Polytechnic Institute, is also included. The papers describe leading-edge research on face and human activity recognition, challenges in implementing appropriate technology projects in developing countries, complex networks, engineering bacteria for drug production, organic-based solar cells, and current status and future challenges in fuel cells, among other topics. Appendixes include information about contributors, the symposium program, and a list of meeting participants. This is the eleventh volume in the USFOE series.
Keywords: Engineering and Technology; Space and Aeronautics

Transit Research Analysis Committee Letter Report: March 10, 2006 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB’s Transit Research Analysis Committee (TRAC) has delivered a letter report to Ronald Hynes, the deputy associate administrator for research, demonstration, and innovation for the Federal Transit Administration (FTA). The March 10, 2006, letter report presents the committee’s response to the September 30, 2005, version of FTA’s strategic research plan, including recommendations for disseminating and updating the plan and putting it into practice by linking it to FTA’s annual program of research. The report also addresses the role of earmarked and designated research within the context of FTA’s efforts to identify and conduct a balanced portfolio of research to meet the agency’s strategic goals and serve the transit community. In addition, the report explores opportunities to pursue research in support of three of FTA’s high-level goals--increasing ridership, improving capital and operating efficiencies, and protecting the environment and promoting energy independence. On this last topic, the report includes a discussion focused on transit applications of electric drive technologies.
Keywords: Transportation and Infrastructure

The Richard and Hinda Rosenthal Lectures 2005: Next Steps Toward Higher Quality Health Care - Institute of Medicine; Institute of Medicine (The National Academies Press, 2006)
In 1988, an exciting and important new program was launched at the Institute of Medicine. Through the generosity of the Richard and Hinda Rosenthal Foundation, a lecture series was established to bring to greater attention some of the critical health policy issues facing our nation today. Each year a subject of particular relevance is addressed through a lecture presented by experts in the field.
Keywords: Health and Medicine

Law, Science, and Disaster: Summary of the October 18, 2005 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2006)
The Disasters Roundtable convened its 15th workshop on Law, Science, and Disaster on October 18, 2005. It is recognized that science and technology can provide part of the basis for more effective hazard-related laws and regulations, including zoning laws, building codes, and hazard disclosure requirements. It is also clear that issues unrelated to science and technology also drive the development of hazard and disaster law. This workshop examined recent developments and trends in hazard and disaster law and its implementation, and drew on the September 11, 2001 experience to discuss the related issue of victim compensation.
Keywords: Earth Sciences; Conflict and Security Issues

Community Disaster Resilience: A Summary of the March 20, 2006 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2006)
Keywords: Earth Sciences; Conflict and Security Issues

Changes to the Mechanistic Empirical Pavement Design Guide Software Through Version 0.900, July 2006 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 308: Changes to the Mechanistic Empirical Pavement Design Guide Software Through Version 0.900, July 2006, summarizes numerous changes made to the original Version 0.7 of the Mechanistic-Empirical Pavement Design Guide (MEPDG) software. Specifically, the digest describes the corrections incorporated in Version 0.8 (released in November 2005) and the mainly technical improvements and enhancements included in Version 0.900 (released in July 2006).
Keywords: Transportation and Infrastructure

Committee on the Review of the U.S. DOT Strategic Plan for Research and Development Letter Report: August 2006 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2006)
An August 2, 2006, letter report from TRB's Committee on the Review of the U.S. Department of Transportation (USDOT) Strategic Plan for Research, Development, and Technology presents the committee's findings on its review of the USDOT's 5-year strategic plan for federal transportation research, development, and technology (RD&T). The letter report also offers the committee's view of what a strategic plan could and should be to help the USDOT in future strategic planning. In addition, the report provides advice on potential roles for the Research and Innovative Technology Administration (RITA) in developing and implementing strategic USDOT RD&T plans in the future.
Keywords: Transportation and Infrastructure

International Human Rights Network of Academies and Scholarly Societies: Proceedings - Symposium and Seventh Biennial Meeting, London, May 18-20, 2005 (The National Academies Press, 2006)
This report is the proceedings of the seventh biennial meeting of the International Human Rights Network of Academies and Scholarly Societies. (The international Network, created in 1993, consists of 70 national academies and scholarly societies around the world that work to address serious science and human rights issues of mutual concern. The Committee on Human Rights of the U.S. National Academies serves as the Network's secretariat.) The meeting was held on May 18 and 20, 2005, at the Royal Society in London. The main events of the meeting were a semipublic symposium, entitled Scientists, Human Rights, and Prospects for the Future, and a workshop on a variety of topics related to science, engineering, and health in the human rights context.
Keywords: Behavioral and Social Sciences

The Indian Ocean Tsunami Disaster: Implications for U.S. and Global Disaster Reduction and Preparedness: Summary of the June 21, 2005 Workshop of the Disasters Roundtable - National Research Council (The National Academies Press, 2006)
The Indian Ocean earthquake and tsunami resulted in one of the greatest "natural" disasters that the world has seen in modern times. The impact of the catastrophe was felt world wide, with scores of nationals from other countries, many drawn to the impacted areas by tourist attractions, among the dead and injured, and unprecedented government and non-government disaster relief and recovery efforts mounted from every corner of the globe. On June 21, 2005 The Disasters Roundtable convened a workshop to consider: (1) knowledge gained by researchers investigating various aspects of the disaster and its implications for implementing effective tsunami mitigation, detection, warning, and emergency response systems, (2) emerging U.S. initiatives and how they are expected to tie into regional and global efforts to reduce the impacts of such disasters, and (3) implications of the disaster for multi-hazard mitigation and preparedness at the national and international scale.
Keywords: Earth Sciences

Assessment of the Benefits of Extending the Tropical Rainfall Measuring Mission: A Perspective from the Research and Operations Communities: Interim Report - National Research Council (The National Academies Press, 2006)
Launched jointly in 1997 by the National Aeronautics and Space Administration (NASA) and the Japan Aerospace Exploration Agency (JAXA), the Tropical Rainfall Measuring Mission (TRMM) is a satellite mission that placed a unique suite of instruments, including the first precipitation radar, in space. These instruments are used to monitor and predict tropical cyclone tracks and intensity, estimate rainfall, and monitor climate variability (precipitation and sea surface temperature). TRMM has been collecting data for seven years; this data is used by the Joint Typhoon Warning Center, the National Center for Environmental Prediction, and the National Hurricane Center, among others worldwide. In July 2004, NASA announced that it would terminate TRMM in August 2004. At the request of the National Oceanic and Atmospheric Administration (NOAA), the White House, and the science community, NASA agreed to continue TRMM operations through the end of 2004. Meanwhile, NASA asked a National Research Council (NRC) committee to provide advice on the benefits of keeping TRMM in operation beyond 2004. After holding a workshop with a number of experts in the field, the committee found that TRMM will contribute significantly to operations and science if the mission is extended; and therefore, strongly recommends continued operation of TRMM with the caveat that cost and risk will need to be further examined before a final decision about the future of TRMM can be made.
Keywords: Earth Sciences

Priorities in Space Science Enabled by Nuclear Power and Propulsion - National Research Council (The National Academies Press, 2006)
In 2003, NASA began an R&D effort to develop nuclear power and propulsion systems for solar system exploration. This activity, renamed Project Prometheus in 2004, was initiated because of the inherent limitations in photovoltaic and chemical propulsion systems in reaching many solar system objectives. To help determine appropriate missions for a nuclear power and propulsion capability, NASA asked the NRC for an independent assessment of potentially highly meritorious missions that may be enabled if space nuclear systems became operational. This report provides a series of space science objectives and missions that could be so enabled in the period beyond 2015 in the areas of astronomy and astrophysics, solar system exploration, and solar and space physics. It is based on but does not reprioritize the findings of previous NRC decadal surveys in those three areas.
Keywords: Space and Aeronautics

Innovating for Profit in Russia: Summary of a Workshop - National Research Council (The National Academies Press, 2006)
The National Research Council hosted an interacademy workshop in Yekaterinburg, Russia together with the Russian Academy of Sciences in October 2004 as a means of exploring various aspects of industrial innovation in the Urals region of Russia. Workshop presenters focused on the establishment of cooperative business partnerships between Russian industrial companies and Russian research organizations, particularly those in the closed nuclear cities of Russia. The concept of "market pull" was therefore an important aspect of the workshop, including partnerships between Russian researchers and international companies, as well as those with international research centers. However, given the complex economic and research climates in Russia, which are intensified in the nuclear cities, cooperation between Russian industry and Russian researchers were of primary during the workshop presentations and subsequent discussions as captured in this workshop summary.
Keywords: Biology and Life Sciences

Condensed-Matter and Materials Physics: The Science of the World Around Us: An Interim Report - National Research Council (The National Academies Press, 2006)
As part of the 2010 physics decadal survey project, DOE and NSF requested the NRC to assess opportunities, over roughly the next decade, in condensed matter and materials physics (CMMP). The study is to review recent accomplishments and new opportunities; identify potential future impact of CMMP; consider its contributions to national needs; assessing priorities for tools and facilities; analyze current research and funding; and make recommendations for realizing the full benefit of CMMP. This interim report provides a summary of the early assessment of eight important challenges facing CMMP research in the coming decade and a brief review of the international situation. The final report will present a detailed discussion of these challenges including recommendations for addressing them.
Keywords: Engineering and Technology; Math, Chemistry, and Physics

Toward a New Advanced Hydrologic Prediction Service (AHPS) - National Research Council (The National Academies Press, 2006)
The National Weather Service (NWS) is responsible for providing flood forecasts and warnings in the United States. The agency established the Advanced Hydrologic Prediction Services (AHPS) program in 1997 to advance technology for hydrologic services, specifically to provide accurate forecasts that support timely warnings for all users of hydrologic predictions. AHPS strives to provide information at the right time to facilitate adequate responses to mitigate damages to life, livelihoods, and property. AHPS is slated to be fully implemented nationwide in 2013. With seven years still remaining in its development and implementation timeline, a review of the program now is critical to providing NWS with information it needs to maximize the effectiveness of the AHPS program. This report assesses AHPS in respect to hydrologic science and technology research, river routing and mechanics, "systems" engineering aspects, and implementation. Overall, this report finds AHPS to be an ambitious program that promises to provide services and products that are timely and necessary. The report calls for AHPS to develop a detailed and comprehensive, multi-year implementation plan and for the program's goals and budget to be brought into closer alignment.
Keywords: Earth Sciences

Extreme Waves - Smith, Craig B. (The National Academies Press, 2006)
Waves are hypnotic and beautiful. They can also be great fun. But Hurricanes Katrina and Rita taught us that they can be powerful and deadly while the 2004 tsunami proved that some waves are absolutely devastating. Science is the best tool for understanding and predicting the most extreme waves. Where do waves come from? Why are some big and some small? From winter to summer, the nature of the beach changes, sculpted by the tireless energy of waves. Most waves are simply rhythmic expressions of Earth’s movement through space and the changes they bring to our shorelines are gradual. But given the right weather conditions and combination of natural forces, waves can wreak havoc. These are extreme waves, waves that can stretch 100-feet high—posing an imminent threat to large sea vessels and coastal structures. There are even waves that have stripped trees from mountains as they surged to an estimated 1,700 feet high. But even smaller waves are dangerous to ships and coastlines. Indeed, the lessons of the 2004 Bay of Bengal tsunami and the damage wrought by recent tidal surges in New Orleans underscore the need for better tracking and prediction of extreme waves. Extreme Waves is a fascinating history of waves. Covering both the headline stories as well as incidents that are less well-known but equally startling Craig Smith, author and amateur sailor, will have you riveted from the first chapter to the last.
Keywords: Explore Science; Earth Sciences